2017
DOI: 10.1080/03639045.2017.1359621
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polyvinylpyrrolidone, microcrystalline cellulose and colloidal silicon dioxide on technological characteristics of a high-dose Petiveria alliacea tablet

Abstract: The use of adequate amounts of PVP, MC and CSD as per the factorial design allowed the preparation of a tablet suitable for administration, despite the inappropriate flow and compressibility properties of the P. alliacea powder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Results of proximate and elemental analysis are shown in Table 5. Value of total ash found for the P. alliacea powder was similar to that recently reported (13.50 vs. 12.04%) for stems and leaves of the plant, indicating a low content of inorganic contaminants (García-Pérez et al, 2017). Volatile compounds were higher in phase C, while phase B showed the most important content of fixed carbon.…”
Section: Dayssupporting
confidence: 87%
See 1 more Smart Citation
“…Results of proximate and elemental analysis are shown in Table 5. Value of total ash found for the P. alliacea powder was similar to that recently reported (13.50 vs. 12.04%) for stems and leaves of the plant, indicating a low content of inorganic contaminants (García-Pérez et al, 2017). Volatile compounds were higher in phase C, while phase B showed the most important content of fixed carbon.…”
Section: Dayssupporting
confidence: 87%
“…Hemoglobin (g L −1 ) Hematocrit (%) Platelet (× 10 3 mm 3 ) Leukocytes (× 10 9 L −1 ) Neutrophils (× 10 9 L −1 ) Lymphocytes (× 10 9 L −1 ) P. alliacea. The mean value of phenolic content in a powder of P. alliacea leaves and stems was determined to be 0.33% (García-Pérez et al, 2017). These molecules are present as simple phenols, short conjugated systems and polycondensed structures (polymeric tannins).…”
Section: Groups Sexmentioning
confidence: 99%
“…Fitoterapija, kao jedna od alternativnih terapija, pomaže u poboljšanju funkcije imunološkog sistema pacijenta, smanjujući oksidativni stres, čime se usporava napredovanje bolesti, poboljšava nutritivni status, i postiže bolja tolerancija na konvencionalne terapije [11].…”
Section: Anamuunclassified
“…Konkretno, svoj-anamu, moringa, spirulina i hlorela: doprinos kvalitetu života onkoloških pacijenata rezultati postmarketinške prospektivne studije u srbiji, 2021 -2022. godine anamu, moringa, spirulina, and chlorella: contribution to the quality of life of oncology patients results of the post-marketing prospective study performed in serbia in 2021 -2022 triterpenes (isobornyl, isobornyl acetate, isobornyl cinnamate, alpha-friedelinol); sulfur derivatives (benzyl-2-hydroxy-5-ethyl-trisulfide, dibenzyl trisulfide); flavonoids (astilbin, gelatin, leridal, leridol, leridol-5-methyl-ether, myricitrin); inorganic compounds (potassium nitrate); lipids (lignoceric acid, lignoceryl lignocerate, linoleic acid, nonadecanoic acid, oleic acid, palmitic acid, stearic acid); benzene derivatives (benzaldehyde, benzoic acid); alkanes (lignoceryl alcohol); carbohydrates (pinitol). In particular, properties such as immunostimulation are attributed to tannins, polyphenols and benzyl-2-hydroxy-5-cetyl-trisulfide, which are found in the leaves and young stems of the plant [10,11]. At the National Center for Scientific Research of Cuba, a study was conducted on anamu plant extracts which revealed the presence of elements such as selenium (Se), zinc (Zn), copper (Cu), iron (Fe) and magnesium (Mg), which affect the immune system [10].…”
Section: Anamumentioning
confidence: 99%
See 1 more Smart Citation